2018
DOI: 10.1038/s41598-018-36197-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating antimalarial efficacy by tracking glycolysis in Plasmodium falciparum using NMR spectroscopy

Abstract: Glucose is an essential nutrient for Plasmodium falciparum and robust glycolytic activity is indicative of viable parasites. Using NMR spectroscopy, we show that P. falciparum infected erythrocytes consume ~20 times more glucose, and trophozoites metabolize ~6 times more glucose than ring stage parasites. The glycolytic activity, and hence parasite viability, can be measured within a period of 2 h to 5 h, using this method. This facilitates antimalarial bioactivity screening on ring and trophozoite stage paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Cell Host & Microbe Review 2015). DHA-treated ART-sensitive 3D7 parasites were found to have reduced but not ablated glycolytic flux (Shivapurkar et al, 2018). These data point to ART resistance being an actively maintained, cytoprotective, metabolically dampened but not quiescent state that primarily protects early rings.…”
Section: Art-the Core Component Of Current First-line Antimalarial Comentioning
confidence: 76%
“…Cell Host & Microbe Review 2015). DHA-treated ART-sensitive 3D7 parasites were found to have reduced but not ablated glycolytic flux (Shivapurkar et al, 2018). These data point to ART resistance being an actively maintained, cytoprotective, metabolically dampened but not quiescent state that primarily protects early rings.…”
Section: Art-the Core Component Of Current First-line Antimalarial Comentioning
confidence: 76%
“…This is consistent with nonhuman primate Plasmodium coatneyi infection studies, where increased splenic FDG uptake associated with accumulation of iRBCs in the red pulp and lymphoid hyperplasia have been reported [ 16 ]. In vitro studies have shown that iRBCs consume up to 100 times the amount of glucose than that consumed by uninfected erythrocytes [ 28 ] and that trophozoite uptake is up to 6-fold greater than that of ring stages [ 29 ]. While no Plasmodium studies have been performed to identify if this in vitro glucose consumption is sufficient to be detected by FDG PET, the principle of clinically detectable tracer uptake by pathogens has been demonstrated in bacteria [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of D-glucose and L-lactate in spent medium were monitored using commercial enzymatic assays in two independent experiments. As glycolytic activity in P. falciparum typically peaks during intra-erythrocytic trophozoite development (Shivapurkar et al, 2018), we collected samples at 30, 34, 38 and 42 hpi to cover this developmental stage. Results showed that spent medium samples from 3D7 Δ PflipB contained significantly less D-glucose and more L-lactate than 3D7 WT at 42 hpi (Fig.…”
Section: Resultsmentioning
confidence: 99%